NILAI PENDIDIKAN BISNIS KELUARGA PENGUSAHA PERAK HS SILVER DI KOTAGEDE - Birsyada, Muhammad Iqbal; Siswanta, Siswanta (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2020)
Socio-historically the silver business has been the identity of the creative economy industry in Kotagede. This study aims to find a causal relationship between the business behaviors of silver HS silver entrepreneurs in Kotagede with family education values. In addition, this study want to find the process of inheritance business values in the family of silver HS Silver entrepreneurs in Kotagede. This design uses a qualitative method with a phenomenological approach. The procedure of this study focuses on the study of the phenomenon of the behavior of silver entrepreneurs in Kotagede Silver HS. The results of this study include the existence of a causal relationship between business success and Javanese cultural values applied in the family. Second, the founder of the HS company. Silver in daily practice inherits and instills the character values of good business education with families and all employees through examples in doing business. The values of business education include: honest, patient, humble, clean, neat, thorough, strong intention, innovative, and hard work. Third, the development of HS. Silver is increasingly advanced because the quality of management used is very good and the products produced always adjust to market developments.Keywords: Values, Education, Family Business, Entrepreneurs, Silver.